Health system challenges for improved childhood pneumonia case management in Lagos and Jigawa, Nigeria. Issue 1 (28th January 2020) - Shittu, Funmilayo; Agwai, Imaria C.; Falade, Adegoke G.; Bakare, Ayobami A.; Graham, Hamish; Iuliano, Agnese; Aranda, Zeus; McCollum, Eric D.; Isah, Adamu; Bahiru, Solomon; Ahmed, Tahlil; Burgess, Rochelle A.; et al.
Abstract: Background: Case fatality rates for childhood pneumonia in Nigeria remain high. There is a clear need for improved case management of pneumonia, through the sustainable implementation of the Integrated Management of Childhood Illnesses (IMCI) diagnostic and treatment algorithms. We explored barriers and opportunities for improved case management of childhood pneumonia in Lagos and Jigawa states, Nigeria. Methods: A mixed‐method analysis was conducted to assess the current health system capacity to deliver quality care. This was done through audits of 16 facilities in Jigawa and 14 facilities in Lagos, questionnaires (n = 164) and 13 focus group discussions with providers. Field observations provided context for data analysis and triangulation. Results: There were more private providers in Lagos (4/8 secondary facilities) and more government providers in Jigawa (4/8 primary, 3/3 secondary, and 1/1 tertiary facilities). Oxygen and pulse oximeters were available in two of three in Jigawa and six of eight in Lagos of the sampled secondary care facilities. None of the eight primary facilities surveyed in Jigawa had oxygen or pulse oximetry available while in Lagos two of three primary facilities had oxygen and one of three had pulse oximeters. Other IMCI and emergency equipment were also lacking including respiratory rate timers, particularly in Jigawa state. Health care providers scored poorly on knowledge of IMCI, though previous IMCI training was associated with better knowledge. Key enabling factors in delivering pediatric care highlighted by health care providers included accountability procedures and feedback loops, the provision of free medication for children, and philanthropic acts. Common barriers to provide care included the burden of out‐of‐pocket payments, challenges in effective communication with caregivers, delayed presentation, and lack of clear diagnosis, and case management guidelines. Conclusion: There is an urgent need to improve how the prevention and treatment of pediatric pneumonia is directed in both Lagos and Jigawa. Priority areas for reducing pediatric pneumonia burden are training and mentoring of health care providers, community health education, and introduction of oximeters and oxygen supply.